Стратегическое планирование в российских предпринимательских структурах (Путеводитель предпринимателя)
In article features of strategic planning of activity of enterprise structures of Russia are analysed. Definition of strategic planning is presented, the algorithm of decision-making in the field of strategic planning is resulted, the basic tendencies of practice of strategic planning in the companies of the Russian Federation are revealed.